ANALYSIS TO IMPROVE THE PERFORMANCE OF LEDOOKOMBO DISTRICT VILLAGE EQUIPMENT USING MOTIVATION AND JOB TRAINING DISCIPLINE VARIABLES - Robbani, Ahmad Faydhur; Reskiputri, Tatit Diansari; Winahyu, Pawestri (Universitas Muhammadiyah Tangerang, 2024)
This research was conducted to determine the influence of work discipline, work motivation and work training on improving the performance of village officials in Ledokombo District. The research method used in this research is a quantitative method with a census sampling method of 117 respondents, using a questionnaire sheet distributed to village officials in Ledokombo District. This research uses multiple linear regression analysis methods, partial tests, and coefficient of determination (R2) tests. And the results of the analysis using SPSS 27 show that the three variables, namely motivational discipline and work training, have a significant influence on the performance of village officials in Ledokombo District. The results of the determination test (r2) were (41.8%) showing the large proportion or percentage contribution of the Discipline, Motivation and Job Training variables to performance. Meanwhile (58.2%) was contributed by other variables not included in this research, for example work burnout, compensation, work commitment and so on.